Identifikasi Risiko Menggunakan IBPRP dan JSA Berdasarkan PERMEN PUPR NO. 21 Tahun 2019 (Studi Kasus: Pekerjaan Struktur Fondasi Pada Proyek Pembangunan Gedung Layanan Pembelajaran Fakultas ISIP Universitas Jendral Soedirman Purwokerto) - Riyan Riski Kurniawan; Adwitya Bhaskara (Jurnal Ilmiah Rekayasa Sipil, 2021)
ABSTRACT Construction project of building frequently has risk. Often occurring risk often is job accident. Job accident may be one of causes inhibiting project job activity. According to the data of Social Health Organizing Agency for labor, the job accident rate was 130.926 in 2017. Application of a good Construction Safety Management System is expectable to minimize resulting risk probability. This study used method of Danger Identification and Opportunity Risk Assessment (IBPRP) and Job Safety Analysis (JSA) deriving from PURR Government Regulation Number 21/2019. This study aimed at finding IBPRP and JSA designs as well as analogy of problem identification and control variables of foundation job in the Construction Project of Learning Service Building (FISIP) of General Soedirman University of Purworejo. The results of IBPRP and JSA analysis indicated that risk identification and risk rate of foundation job in construction project of Learning Service Building (FISIP) of General Soedirman University of Purwokerto, the foundation job had 48 risks identified from 11 job sequences. All of the 49 identified risks were in low risk rate, where rate value of matrix 2 (two) and 14 risks had rate value of matrix 4 (four). Keywords: Construction Safety Management System (SMKK), risk, risk rate, risk matrix, IBPRP, JSA.